Quality of Life in Newly Diagnosed Patients With Parkin-Related Parkinson's Disease - Zhou, Xin-Yue; Liu, Feng-Tao; Chen, Chen; Luo, Su-Shan; Zhao, Jue; Tang, Yi-Lin; Shen, Bo; Yu, Wen-Bo; Zuo, Chuan-Tao; Wu, Jian-Jun; Ding, Zheng-Tong; Wang, Jian; et al. (Frontiers in Neurology, 2020)
Introduction: Mutations in the Parkin gene are the most common cause of autosomal recessive early-onset Parkinson’s disease (PD). However, little is known about the quality of life (QoL) in Parkin-related PD. Here, we investigated the patterns of QoL in newly diagnosed Parkin-related PD patients. Methods: Newly diagnosed PD patients (diagnosis made within 12 months) who had an age of onset (AOO) below 40 and underwent a PD-related genetic testing, were recruited (n=148). Among them, 24 patients carried bi-allelic variants in Parkin (PD-Parkin) and 24 patients did not have any known causative PD mutations, or risk variants (GU-EOPD). The clinical materials, relevant factors and determinants of QoL were analyzed. Results: PD-Parkin patients had a younger AOO (p=0.003) and longer disease duration (p=0.005). After adjustment for AOO and disease duration, more dystonia (p=0.034), and worse scores of non-motor symptoms including Beck depression inventory (BDI, p=0.035), Epworth sleepiness scale (ESS, p=0.044), and subdomains of depression/anxiety (p=0.015) and sleep disorders (p=0.005) in Non-motor symptoms questionnaire, were found in PD-Parkin comparing with GU-EOPD. PD-Parkin patients had poorer QoL (adjusted p=0.045), especially in the mobility (adjusted p=0.025), emotional well-being (adjusted p=0.015) and bodily discomfort dimensions (adjusted p=0.016). BDI scores (p=0.005) and ESS scores (p=0.047) were significant determinants of QoL in PD-Parkin. Conclusion: Newly diagnosed PD-Parkin patients showed worse QoL. More depression and excessive daytime sleepiness predicted worse QoL. For clinicians, management of depression and excessive daytime sleepiness is suggested to better improve QoL in patients with Parkin mutations.